SELECTION OF POTATO GENOTYPES AT SIX WIDELY SEPARATED LOCATIONS IN NORTHWESTERN CANADA - HARRIS, R. E. (Canadian Journal of Plant Science, 1974)
Norgold Russet and six potato (Solanum tuberosum L.) seedlings were grown and evaluated at six widely separated locations in Northwestern Canada for 3 yr. The total number of tubers decreased with increasing latitude but not their marketable number, nor their total and marketable weight. Similarly, tuber type, specific gravity, boiled quality, or general evaluation did not vary with latitude. The personal bias of observers in rating tuber type and general evaluation was largely eliminated by providing detailed instructions to the six observers, by not including disease in general ratings, and by rating on the marketable tubers. There was close agreement in the performance and evaluation of genotypes between Prince George, Beaverlodge, Anzac, Mile 1019 and Fort Simpson but not between Fort Vermilion and any of the above locations. It was concluded that potato genotype evaluation was needed at two locations in northwestern Canada, one at Fort Vermilion and another at any of the other locations, and that potato research at the other locations should be directed towards improving cultural practices.